Sinology with Engineering Characteristics: Commentary on Jue Hou's "The Cybernetic Writing Pad". Issue 3 (3rd July 2021) - Mitcham, Carl
Abstract: Jue Hou's study of interactions between computer engineers and Chinese script reformers in the 1970s enriches growing STS and China studies interest in Chinese engineering. It can also make a distinctive sinological contribution to contemporary efforts to develop the field of comparative philology.